Q. 305.0( 1 Vote )

Prove that (1 + t

Answer :

Taking LHS

(1 + tan A – sec A)(1 + tan A + sec A)


Using (a – b)(a + b) = a2 – b2


= (1 + tan A)2 – sec2A


= 1 + tan2A + 2 tan A – sec2A


= sec2A + 2 tan A – sec2A


= 2 tan A


= RHS


OR


Taking LHS







= 2 sec2θ


= RHS


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Heights and Distances - IHeights and Distances - IHeights and Distances - I54 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses